Consumer Inertia, Choice Dependence, and Learning from Experience in a Repeated Decision Problem - Miravete, Eugenio J.; Palacios-Huerta, Ignacio (The Review of Economics and Statistics, 2014)
Understanding when and how individuals think about real-life problems is a central question in economics. This paper studies the role of inertia (inattention), state dependence, and learning. The empirical setting is a tariff experiment, when optional measured tariffs for local telephone calls were introduced unanticipatedly. We find that consumers tend to align their choices of tariff and telephone use levels correctly. Despite low potential savings, mistakes are not permanent, as individuals actively engage in tariff switching in order to reduce the monthly cost of telephone service. Ignoring unobservable heterogeneity and the endogeneity of past choices would have reversed these results.